Effect of the Carbon Source on the Characteristics of Silica-carbon as a Handphone’s Case Material - Srie Muljani,; Erwan Adi Saputro,; Kusuma Wardhani Mas’udah,; Syuaibatul Islamiyah, (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Activated carbon is believed to reduce radiation from cell-phone because it has large pores. This study aims to synthesize a silica-carbon composite as a mobile phone casing using activated carbon from bamboo, coconut shells, and coal combined with silicone rubber. The addition of activated carbon is carried out in the range of 10 - 30 g. Activated carbon mixed with silicone rubber and stirred for 3 minutes at 150 rpm. Based on Digital Electromagnetic Radiation, the highest addition of activated carbon (30g) provides a high radiation reduction but has a small tensile strength and a large elongation value. SEM images show that the distribution of activated carbon 10 - 15 g is more homogeneous on the mobile phone casing.